Soft-tissue augmentation for increasing keratinized tissue around dental implants: A systematic review - Farjad Zafar; Maryam Riaz; Rafay Ahmed; Rahul Kumar (Journal of Indian Society of Periodontology)
Background: This systematic review aims to comprehensively assess the efficacy of soft-tissue augmentation procedures in enhancing the width of keratinized mucosa (KM) surrounding implants with compromised soft-tissue status. Materials and Methods: A thorough search was conducted on MEDLINE through PubMed and EMBASE via Ovid, supplemented by manual article searches. Inclusion criteria comprised human studies published in English within the past decade (up to July 2023), focusing on soft-tissue grafting techniques for augmenting keratinized mucosal width. The Joanna Briggs Institute critical appraisal tools were employed to evaluate the risk of bias in selected studies. Results: The review includes 27 studies, comprising nine prospective clinical studies, 13 randomized controlled trials (RCTs), and 5 case series. Notably, interventions demonstrated an augmented KM ranging from 0.89 mm to 7.7 mm. Optimal outcomes were observed with apically positioned partial-thickness flaps and vestibuloplasty (VP) utilizing xenogeneic collagen matrix (XCM) or free gingival graft (FGG). However, heterogeneity in study designs precluded meta-analysis. Conclusion: Despite the limitations, this study emphasizes the potential to augment KM width through apically positioned partial-thickness flaps and VP techniques employing XCM or FGG. Further RCTs with extended follow-up are needed to refine treatment approaches, improve outcomes, and address gaps in understanding graft integration mechanisms and strategies to minimize graft shrinkage.